(untitled) (Journal of Academic Research, 2024)
Special education and giftedness detection...future visions There is no doubt that taking care of the gifted is one of the basics of the qualitative renaissance of any society and is a measure of the progress and advancement of nations. The importance of the study lies in the lack of attention to this category, which many rely on, and the discovery of the gifted, as there are no special tests to identify them, and there are no curricula with cognitive information that develops creativity, and there is no real encouragement and incentives for students who show new attitudes. The study aimed to: What are the most prominent psychological needs of the gifted? How to detect talented people? Future visions for the gifted? Note that the researcher used the descriptive approach, and reviewed a number of previous studies, and to achieve the first goal of the study, the gifted person must be provided with protection and psychological security from several aspects, and helped him express his ideas, understand his personality, and his ability to challenge circumstances. ‏The second goal is to detect gifted people through the application of multiple methods, tests, and standards, and the role of the family, school, and university. As for the third goal, the future vision for the gifted is to prepare an elite group of the future generation who are promising talent with high-quality educational, scientific, and creative achievements through creating an appropriate educational environment and using the latest educational methods for growth. And developing the capabilities of the gifted and nurturing them, what is the perception and aspiration for the future through self-affirmation, gaining ability, a sense of responsibility, and developing ways of thinking. The researcher proposes forming work teams of specialists and officials in the Ministry of Education and Higher Education for an integrated action plan that addresses aspects of identifying this important group in society and establishing a school project for the gifted. With a qualified educational staff trained in teaching methods and an enrichment curriculum ,Among the most important recommendations of the study: building a plan to care for the gifted based on classifying gifted students, seeking to provide specialized scientific references in the field of giftedness and establishing a scientific library, taking into account the different lifestyles of the gifted and working to develop high-level models of thinking, increasing the funds allocated to gifted care programs and opening centers to care for them. ….. Keywords: special education, gifted people, future vision